Analysis of the Regional Revenue and Expenditure Budget Realization Report at the Sinjai Regency Tourism and Culture Office, Indonesia - A. Fara Rezky Rahmadani Rasyid; Agusdiwana Suarni; Nasrullah (www.amertainstitute.com, 2024)
Purpose: The Purpose of this study is to determine the efficiency of budget use in the 2019 2023 period at the Sinaji Regency Tourism and Culture Office, with a focus on collecting budget allocations, realization, and efficiency in each budget year. Design/methodology/approach: The type of research used is quantitative with an explanatory study approach through documentation of financial recapitulation reports from the Sinjai Regency Tourism and Culture Office. Findings: The result of the study show that despite fluctuations in budget allocation, the level of budget efficiency remains stable, ranging from 95.73% to 98.89%. 2019 recorded an efficiency of 95.73%, followed by an increase in 2020 (96.95%) due to budget adjustments related to the COVID-19 pandemic. In 2021, efficiency was recorded at 98.38%, with allocations focused on programs supporting government affairs. 2022 achieved the highest efficiency of 98.89%, while in 2023, despite a budget spike, efficiency remained at 97.06%. The programs that received the largest budget allocations during this period were the office services and tourism destination development programs, with fairly efficient budget management despite implementation challenges in 2023. Overall, this study shows that budget management during this period has been carried out efficiently. Social implications: This study argues that budget efficeincy in the Sinjai Regency Tourism and Culture Office has a direct impact on the development and sustainability of local tourism and cultural initiatives. By ensuring high efficiency in budget allocation and realization, resources can be optimized to support programs that enhance community engagement, preserve cultural heritage, and boots the local economy. Originality/Value: This study makes a unique contribution by presenting a quantitative analysis of budget efficiency over five years, including the impact of the COVID-19 pandemic on public spending. It highlights the stability of efficiency levels despite external challenges, and identifies areas for improvement in the management of large-scale programs.